Physicochemical and sensory evaluation of wine brandies aged using oak and chestnut wood simultaneously in wooden barrels and in stainless steel tanks with staves. (7th October 2016) - Canas, Sara; Caldeira, Ilda; Anjos, Ofélia; Lino, João; Soares, Amélia; Pedro Belchior, António
Summary: This study provides innovative information on the simultaneous use of Limousin oak and chestnut wood in the ageing of wine brandy. Ageing was performed in 650‐L wooden barrels and in 3000‐L stainless steel tanks with staves over a 2‐year period. Effect of both kinds of wood in the brandy features depended on the ageing technology. Stainless steel tanks with staves originated lower enrichment of the brandy in dry extract (0.89 vs. 1.25 g L −1 ), total phenolics (22.33 vs. 29.40) and low molecular weight extractable compounds (119.83 vs. 231.65 mg L −1 ), but promoted a faster evolution of the analytical colour (lower L*, higher C*, a* and b*) and sensory colour (topaz and greenish vs. golden). The aroma and flavour profiles of the brandy were not significantly influenced by the ageing technology. Therefore, it is a promising option for both ageing technologies because it ensures the quality of brandy, together with a lower cost of the wood and exemption of the blending operation. Abstract : Experimental design and main effects of the simultaneous use of oak and chestnut wood on the ageing of wine brandy.